2018
DOI: 10.4103/jispcd.jispcd_205_18
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting access to oral health care among adults in Abha city, Saudi Arabia

Abstract: Aims and Objectives:To investigate the self-reported access problems to dental care among adults in Abha city, KSA.Materials and Methods:A cross-sectional descriptive survey was carried out among adults in Abha city, Saudi Arabia. A structured, close-ended, self-administered questionnaire elicited the access and utilization of dental care among a sample of adults. Data were collected and analyzed using SPSS version 21.0 statistical software. The descriptive statistics and logistic regression analysis were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
35
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 23 publications
10
35
0
1
Order By: Relevance
“…Of those who did not think they needed dental treatments, three-quarters were not utilizing dental services properly. This is similar to what was reported by other research,[1611] where a lack of perceived need for dental treatment significantly affected seeking dental care. This figure of low access and utilization of dental services among the elderly population of Saudi Arabia might be reflected in their dental care.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Of those who did not think they needed dental treatments, three-quarters were not utilizing dental services properly. This is similar to what was reported by other research,[1611] where a lack of perceived need for dental treatment significantly affected seeking dental care. This figure of low access and utilization of dental services among the elderly population of Saudi Arabia might be reflected in their dental care.…”
Section: Discussionsupporting
confidence: 91%
“…However, Saudi adults utilize dental services more often (56.7%). [11] As there is no literature review article to compare with, comparison with results of other studies is justified. The percentage of those with proper access in our study was lower than that reported in other studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the limitations of this study was that the sample, which mostly comes from the rural area might have some barriers to assess the public oral health service, such as transportation and income problems. [28] However, this study reflected the high demand in preventive and interceptive orthodontic treatment need around this location, which needed the intensive oral health care. Even though, the cause of malocclusion could be identified in genetic basis, many different variables had an influence during malocclusion development.…”
Section: Discussionmentioning
confidence: 99%
“…2 Also, the high prevalence of the periodontal disease, excessive tooth loss, dental caries experiences, oral cancers and xerostomia are the major issues reported among adult populations particularly in older ages with poor oral health, globally. 3 Availability of dental care and timely access to oral healthcare facilities preserves the function, morbidity and mortality hence the overall quality of life can be improved. 4 The best possible health outcomes are only possible if the personal health care services are accessible timely.…”
Section: Introductionmentioning
confidence: 99%